2008
DOI: 10.3390/md6010001
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Cytotoxic Assessment of Marine Cyanobacteria - Synechocystis and Synechococcus

Abstract: Aqueous extracts and organic solvent extracts of isolated marine cyanobacteria strains were tested for antimicrobial activity against a fungus, Gram-positive and Gram-negative bacteria and for cytotoxic activity against primary rat hepatocytes and HL-60 cells. Antimicrobial activity was based on the agar diffusion assay. Cytotoxic activity was measured by apoptotic cell death scored by cell surface evaluation and nuclear morphology. A high percentage of apoptotic cells were observed for HL-60 cells when treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 25 publications
1
52
0
1
Order By: Relevance
“…and Synechococcus spp. had antibacterial activity against Gram-positive bacteria, but not against Gram-negative ones (Martins et al 2008). Similarly, cyanobacteria isolated from benthic mats of Antarctic lakes have been shown to have antimicrobial activity (Biondi et al 2008).…”
Section: Cyanobacteriamentioning
confidence: 99%
“…and Synechococcus spp. had antibacterial activity against Gram-positive bacteria, but not against Gram-negative ones (Martins et al 2008). Similarly, cyanobacteria isolated from benthic mats of Antarctic lakes have been shown to have antimicrobial activity (Biondi et al 2008).…”
Section: Cyanobacteriamentioning
confidence: 99%
“…and R. gracilis. Martins et al (2008) reported inhibition of gram positive bacteria by extracts of marine Synechocystis and Synechococcus, and also observed the variations in the activity of different extracts.…”
Section: Discussionmentioning
confidence: 94%
“…Magalhães et al (2003) reported that S. aquatilis produced microcystin in Sepetiba Bay, Brazil, where were observed regular blooms of these cyanobacteria, and the microcystin was found in fish caught in this bay. Several works of Martins, Pereira, Welker, Fastner, and Vasconcelos (2005), Martins, Fernandez, Beiras, and Vasconcelos (2007) and Martins et al (2008) reported the production of microcystin by the marine cyanobacteria, including genus Synechocystis. Vareli et al (2012) reported the presence of the hepatotoxic microcystins in the Mediterranean Sea, and he suggested a potential association of microcystins with Synechococcus and/or Synechocystis cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the fascinating discoveries regarding biological activity is the anticancer property demonstrated among cyanobacterial genera such as Nostoc, Fhormidium, Gloeocapsa, Anabaena, Spirulina, Synechocystis and Synechococcus (Surakka et al 2005;Martins et al 2008;Gigova et al 2011;Oh et al 2011). Cyanobacteria produce a wide range of cytotoxic compounds, many of which are regarded as promising candidates for drug discovery, with applications in pharmacy, because of their natural origin, uniqueness and structural diversity (Singh et al 2005;Tan 2007;Gademann and Portmann 2008).…”
Section: Introductionmentioning
confidence: 99%